2011
DOI: 10.4103/0970-0218.86524
|View full text |Cite
|
Sign up to set email alerts
|

Hand hygiene compliance in the intensive care units of a tertiary care hospital

Abstract: Context:Hand hygiene (HH) is the most important measure to prevent hospital-acquired infections but the compliance is still low.Aims:To assess the compliance, identify factors influencing compliance and to study the knowledge, attitude and perceptions associated with HH among health care workers (HCW).Settings and Design:Cross-sectional study conducted in 42 bedded Medical (Pulmonary, Medicine and Stroke) intensive care units (ICU) of a tertiary care hospital.Materials and Methods:HCWs (doctors and nurses) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
38
3
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 11 publications
6
38
3
3
Order By: Relevance
“…Several investigators identified that the increase in workload was a negative impact factor on compliance. [20][21] Variables such as the weariness caused by work routines (severity of patient cases, NICU overcrowding, number of shifts per week, number of jobs) were not registered. Also in this study, significantly more observations were performed with nursing technicians in comparison to physicians, and physicians had the higher compliance rates.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators identified that the increase in workload was a negative impact factor on compliance. [20][21] Variables such as the weariness caused by work routines (severity of patient cases, NICU overcrowding, number of shifts per week, number of jobs) were not registered. Also in this study, significantly more observations were performed with nursing technicians in comparison to physicians, and physicians had the higher compliance rates.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Sharma et al proved that good knowledge might not be converted into actions. In her study, 82% doctors and 59% nurses claimed to have knowledge regarding proper hand hygiene technique 8 . However, the figure was not transformed into practices due to several reasons such as heavy workload, lazy attitude, lack of time and inadequate motivation.…”
Section: Discussionmentioning
confidence: 99%
“…are possible under the pressure of high workload (Hugonnet et al ., 2007a). Hand hygiene compliance of ICU nurses was found to be inversely related with the number of their activities (Sharma et al ., ), while daily proportion of infected patients was significantly correlated with nurse : patient ratio of 2, 3 and 4 days prior (Hugonnet et al ., 2007a). Job dissatisfaction, fatigue, burnout, absenteeism and increased error incidence of personnel due to high workload could also contribute to increased infection risk.…”
mentioning
confidence: 99%